ANALISIS PENGENDALIAN KUALITAS CACAT DIMENSI PADA HEADER BOILER MENGGUNAKAN METODE FMEA DAN FTA DI PT. IHI POWER SERVICE INDONESIA (IPSI) - Tatan Zakaria Zakaria; Anita Dyah Juniarti; Bima Setyo Budi (Prodi Teknik Industri, Fakultas Teknik, 2023)
IHI Power Service Indonesia is a company engaged in the Boiler Pressure Part Industry (Fabrication) in every production activity it always strives to produce quality products according to ASME standards (American Society of Mechanical Engineers). Production results are less than the maximum. In the 2020 period the total production was 28,527 tons and the number of defects was 364 tons, in the 2021 period the total production was 22,703 tons and the number of defects was 301 tons. The author uses the Failure Mode And Effect Analysis (FMEA) method and the Failure Tree Analysis (FTA) method. From the results of data processing using a Pareto diagram based on the RPN value obtained from the FMEA method, the dominant type of defect is obtained, namely Hole Distance with an RPN value of 364.5 and Dimension Length with a value of 351.17, then analyzed using FTA, at the proposed improvement stage it is proposed to use the 5W+1H method. Factors that cause defects include inaccurate and faded measuring instruments, rare maintenance on radial drilling machines and blades that are rarely replaced. Proposed improvements to reduce defects include requesting replacement of measuring instruments, carrying out regular maintenance of radial drilling drilling machines, holding shift schedules for operators, conducting training for operators.